Effect of Gelatin And Egg White Addition on the Characteristics Marshmallow Made from Siwalan and Red Dragon Fruit Peel - Rafi Ahnaf, Muhammad Noval; Rosida (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
Marshmallow is a type of confectionery with a soft, light and chewy texture made from fruits, one of which is siwalan and red dragon fruit skin. In its manufacture, treatment is needed, namely the addition of gelatin and egg white. In this study, marshmallow siwalan and red dragon fruit skin will be made with the treatment of adding gelatin and egg white. The purpose of this study was to determine the effect of gelatin and egg white addition treatment on the physicochemical and organoleptic characteristics of marshmallows produced and to determine the best treatment of marshmallows with the addition of gelatin and egg white favored by panelists. This study used a completely randomized design (CRD) factorial pattern with two factors and two replicates. Factor I is the addition of gelatin (10%, 12%, 14% b/v) and factor II is the addition of egg white (6%, 8%, 10% b/v). If there is a significant difference, it will be continued with the 5% DMRT test. The best treatment results were obtained in the treatment (A2B3) with the addition of gelatin (12%) and egg white (10%), namely Moisture Content 59.44%, Aw Value 0.63, Color Test (a*) 11.63, Chewiness 61.78%, Antioxidant 30,45% and organoleptic values which include Color 5.40, Aroma 4.44, Taste 4.76, Texture 4.28 producing marshmallow siwalan and red dragon fruit skin with the best quality and best panelist acceptance.